Soil carbon and nitrogen near alder, birch and spruce trees in four mixed Norway spruce-dominated stands - Soronen, Päivi; Jämtgård, Sandra; Myllymäki, Mari; Smolander, Aino (Elsevier, 2025)
To increase understanding of soil processes in mixed forests, we examined soil nitrogen (N) and carbon (C) near alder, birch and spruce trees in Norway spruce (Picea abies)-dominated stands in southern Finland. Two sites were middle-fertile stands aged 2040 years, and the other two were fertile stands aged 60 years. Grey alder (Alnus incana) was present at all sites and birch (Betula pendula and Betula pubescens) was present at three sites. At each site, we determined C and N stocks of forest floor and mineral soil (010 cm depth) close to (max distance 1.5 m) alder, birch, and spruce trees. We found forest floor C stocks to be 0.8 kg m−2 higher under alder than under birch trees. Forest floor N stocks were higher near alder than near birch or spruce. Alder decreased C:N-ratio of both forest floor and mineral soil by around 5 units compared to spruce; birch decreased C:N-ratio of mineral soil. Diffusive fluxes of soil N, as determined by microdialysis method, showed no significant differences between species. At the two fertile 60-year-old stands, microbial biomass N was lower near alder than near birch, birch decreased microbial biomass C:N-ratio compared to spruce, and alder decreased C mineralisation rate and dissolved organic C concentration compared to spruce. Several other properties, such as the concentrations of monoterpenes and condensed tannins, were unexpectedly similar under alder, birch and spruce trees. This suggests the presence of complex interactions between trees in mixed forests, driven by above- and belowground processes involving litter dispersal.
Keywords: boreal zone; diffusive flux; mixed forests; nitrogen; organic matter; soil organic carbon